Some basic concepts of fish disease for nutritionists - Mohamed, Shariff (1988)
Disease is olie of most serious limiting factors in the development of aquacumre. Disease is not only restricted to commercial fanns with practice high stocking density but also causes mortalities in laboratory and other experimental systems. Interplay between three main factors. the fish (the host), the enviromnent and the pathogen dctennincs the outbreak of disease. When in a stable situation these factors may interact without resultant disease. However, when there is a change in one or more of the three factors. the delicate balance among them is disrupted and disease may result. Basic understanding of these three factors and their inlenclalionships is important in planning for prevention and control of disease and in making a correct diagnosis.